The Training on the Use of Geogebra Software in Learning at SMA Hutabayuraja : Pelatihan Penggunaan Perangkat Lunak Geogebra dalam Pembelajaran di SMA Hutabayuraja - Lois Oinike Tambunan; Janwar Tambunan (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The use of information technology, especially with computer-based applications in the learning process in schools, is able to provide convenience in the process. In the application of computer-based learning, especially in the learning process in the field of mathematics, the use of information technology, especially the use of mathematical software. One of the mathematical software that can be used in the learning process is the use of Geogebra software. In the learning process in schools, teachers are required to be more innovative and follow the development of information technology in the learning process. The use of Geogebra software can support the learning process, especially in the field of mathematics education. This training aims to make the teachers at SMA Hutabayuraja more skilled in using media in learning. This PKM activity was carried out in a demonstration, where the PKM team first provided material about the GeoGebra software, and continued by providing training using the GeoGebra software to the trainees. Thus, it is hoped that these teachers can use GeoGebra software in the learning process.